EVALUATION OF POLICY OF “SEKOLAH PENGGERAK” AND “GURU PENGGERAK” AS PIONEERS OF CHANGES IN THE EDUCATION SYSTEM IN THE NEW PARADIGM CURRICULUM - Lisa chandrasari Desianti; Tati Rahayuningsih (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The purpose of this paper is to review and evaluated the “Sekolah Penggerak” and “Guru Penggerak” program in Indonesia launched since 2021. The paper attempts to answer the following research questions: (1) has the “Sekolah Penggerak” and “Guru Penggerak” been running as expected? (2) What things need to be done in improving the effectiveness of “Sekolah Penggerak” and “Guru Penggerak” in Indonesia?  This research method is carried out with an evaluation research and desk study approach by reviewing policy objectives rolled out by the Indonesian government through the curriculum "Merdeka Belajar" compared to current conditions.  The results of the desk study and evaluation show that there are at least 7 (seven) aspects that constitute curriculum changes at this program, namely (1) The profile of Pancasila students; (2) Changes in KI and KD to CP (Learning Outcomes); (3) Learning system with thematic approach; (4) The new paradigm curriculum; (5) Collaborative learning model; (6) Informatics subjects; (7) Combining science and social studies subjects. Further research is needed to see the impact and effectiveness of the achievement of the “Sekolah Penggerak” and “Guru Penggerak” in a quantitative method within the next 2 years